Processos e práticas de alfabetização na perspectiva da educação integral: desafios na formação docente - Campos, Rosariane Gláucia Mendonça (2021)
This doctoral research in education presents an overview of literacy policies in relation to the training of literacy teachers. It discusses policies in different historical periods, over the last three decades, which declared the intention to face the literacy problem with new conceptions, new methods and guidelines, culminating in the return of the phonic method in current policies. The general objective of the research was: to identify the understanding of teacher trainers in relation to literacy policies, processes and practices and their repercussions in the context of teacher training practice. As specific objectives, this investigation proposes to: i) analyze the context of the formulation of literacy policies in different federal governments from the 1990s onwards; ii) identify the repercussions of federal policies and programs on teacher training in the municipal education of São Bernardo do Campo/SP; iii) identify, in the discourses of the municipal network trainers, the obstacles and possibilities in teacher training for the establishment of integral, critical and humanizing literacy practices made by Paulo Freire. Based on the epistemology of the Policy Cycle formulated by Stephen Ball and collaborators, the literacy teacher training will be examined in different governments, such as: the National Curriculum Guidelines; the Literacy Teacher Training Program - PROFA; the Literacy Program; National Literacy Pact at the Right Age, National Literacy Pact at the Right Age; National Common Curriculum Base and the common National Literacy Policy, with the Learning Time Program. At a later stage, we try to understand the context of practice, with the consequences of these policies on the training of literacy teachers. Interviews were conducted with three professionals who worked or still work as trainers, with the aim of identifying perceptions of the literacy policies, processes and practices, analyzing how such policies affect the context of training practice. It is a research with a qualitative approach, which intends to describe, analyze and interpret data based on authors such as Paulo Freire, Emilia Ferreiro and Maria do Rosário Longo Mortatti, among others who deal with the subject. The expected results of this research will allow to identify and disseminate the context of the practice of teacher trainers of literacy teachers, verifying how they can reinterpret and recreate policies and possible factors that can lead to literacy processes and practices committed to comprehensive training, for the exercise of participatory citizenship in a democratic society (AU)